Fantastic Mr. Fox - Dahl, Roald; Blake, Quentin (New York : Knopf, 2002)
Three farmers, each one meaner than the other, try all-out warfare to get rid of the fox and his family.
Includes an interview with Roald Dahl.
Keywords: Foxes -- Juvenile fiction; Farmers -- Juvenile fiction; Human-animal relationships -- Juvenile fiction